THE SINGULARITY OF THE SECULAR STATE IN BRAZIL IN THE LIGHT OF THE CONSTITUTION OF 1988 AND THE HISTORICAL AND RELIGIOUS ROOTS OF THE PEOPLE - Barrientos-Parra, Jorge [UNESP] (Revista Brasileira Estudos Politicos, 2015)
This article situates the singularity of the secular State in Brazil in the context of the historical and religious development of the Brazilian people. Indeed the three basic cultures that have formed the Brazilian family, namely the Indigenous, Portuguese and African, all three were imbued with a rich spiritual and religious ethos that has impregnated the soul of the Brazilian as well as the institutions and social and juridical structures of Brazil. Therefore the separation between State and Church in the 21st century in the South American largest country is less an expression of antipathy and heinousness of the secular against the religious or religious against secular, than a political-legal form to ensure awareness freedom and belief and worship freedom of according to the Constitution of Republic of Brazil of 1988.
Keywords: Secular State; Religion; Constitution of Brazil 1988